Inactivation of fruit fly eggs by high pressure treatment - Butz, Peter; Tauscher, Bernhard (Journal of food processing and preservation, 1995)
High-pressure preservation of food could be a new kind of minimal processing to produce high quality convenience food. Pressure treatment of fruits and vegetables can be used to eliminate contamination by insect eggs. At temperatures between 25 and 32.5C, eggs of the Mediterranean fruit fly (Ceratitis capitata) withstand pressure of 100 MPa for 20 min. Larvae and flies of eggs treated this way developed. No survivors were found at pressures in the range of 125-600 MPa. Inactivation was almost independent from time of treatment.